Slower tempo makes worse performance? The effect of musical tempo on cognitive processing speed - Lin, Hung-Ming; Kuo, Su-Hui; Mai, Thao Phuong (Frontiers in Psychology, 2023)
The effects of musical tempo on cognitive processing speed were investigated, and the mediating effect of arousal was empirically tested. In an experiment, participants were divided into fast tempo, slow tempo, and no-music groups and completed three cognitive processing speed tests measuring motor speed, visuospatial processing speed, and linguistic processing speed. The results indicated a significant effect of musical tempo on processing speed and task performance in all three tasks. The slow-tempo group exhibited slower processing speed and worse performance than the no-music group in all three tasks. The fast tempo group displayed no significant difference in processing speed or performance compared with the no-music group. In the linguistic processing task, those who listened to slow-tempo music had better accuracy than those in the other conditions. Arousal did not mediate the relationship between musical tempo and cognitive processing speed.